Analysis of Subsidence Hazards in Pandan Cave Area, Giri Mulyo Village, Marga Sekampung District, East Lampung using Analytical Hierarchy Process - Bilal Al Farishi; Natalia, Happy Christin; Naufal, Rifqi Andi; Aganda, Riyanto Dedinta; Octafiani, Aulia; Hita Kirana; Depri; Pakpahan, Andreas Maruli; Sari, Hissy Ijitiha; Santoso, Nono Agus; Antosia, Risky Martin; Putri, Intan Andriani (UIR PRESS, 2024)
Pandan Cave is a basalt lava cave which is a unique geological tourism area located in Giri Mulyo Village, Marga Sekampung District, East Lampung Regency, Lampung Province. This cave was formed when the lava flow cooled at the top because it was in contact with the cold atmosphere, while at the bottom it was still flowing. This uniqueness caused Pandan Cave to become one of the tourist attractions that was once crowded with tourists. However, the condition of this cave is still very natural which can lead to the risk of geological disasters such as subsidence which can endanger tourists, so it is necessary to research to minimize the occurrence of geological disasters in the area. This research was conducted by observing aerial photographs, collecting data directly in the field, and then processing it with the Analytical Hierarchy Process (AHP). Parameters used in this AHP method include lithology, vegetation, weathering, rock mass class, and cave roof thickness. The existence of subsidence in the study area is influenced by weathering (34%), vegetation (31%), thickness of the cave roof layer (16%), lithology (10%), and rock mass class (9%). Based on the overlay results for each parameter that has been weighted, the Pandan Cave tourism area is divided into three subsidence hazard zone classifications, that is low hazard zone with value of 0.28-0.44, medium hazard zone with range of 0.44-0.60, and high hazard zone with range of 0.60-0.75. Through the Analytical Hierarchy Process (AHP) method and overlay of each parameter used, the distribution of subsidence hazard zones in the study area was obtained. The low threat zone of 27.57 ha is about 57.07% of the total research area, the medium threat zone is 15.86 ha or about 32.83% of the total research area, and the high threat zone is 4.88 ha or about 10. 10% of the total research area.